Factors affecting post-weaning average daily gain and Kleiber ratios in Malpura sheep - PRAKASH, VED; PRINCE, L L L; GOWANE, G R; ARORA, A L (The Indian Journal of Animal Sciences, 2012)
The objective of this study was to determine effect of environmental factors on estimates of post-weaning growth traits. Study suggested that as the age advances growth rate and feed conversion efficiency declines in Malpura sheep. Hence, for higher economic gain selection should be made at earlier age, preferably at 6 month. Rearing male lambs can be more profitable as they achieved higher growth and better feed conversion efficiency. For unbiased estimates of breeding values, correction factors for significant non-genetic factors must be incorporated.